Do crowded classrooms crowd out learning?: evidence from the Food for Education Programme in Bangladesh - Ahmed, Akhter; Arends-Kuenning, Mary (Elsevier, 2006)
Bangladesh’s Food for Education Program (FFE), which provided free food to poor families if their children attended primary school, was successful in increasing children’s school enrollment, especially for girls. However, this success came at a price as class sizes increased. This paper uses a rich data set that includes school achievement test scores, information on schools, and household data to explore the impact of FFE on the quality of education. The analysis focuses on the impact of FFE on the achievement test scores of students who did not receive benefits. We find evidence for a negative impact of FFE on the test scores of non-beneficiary students through peer effects rather than through classroom crowding effects.